Peces del departamento de Caldas, Colombia - Daniel Restrepo-Santamaría (Biota Colombiana, 2011)
The Caldas Department has a rich natural environment, diversity of altitudes above sea level, climates and landscape that provide the region with abundant biotic resources. The presence of Central and Western Andean ranges determines the distribution of water that flows into the two main hydrographic drainages of the department, the Magdalena River basin and the basin of the Cauca River. Based on published studies the ichthyological department drew up for the first time, a list of fish species present in the Department of Caldas. This extensive literature review includes studies of the drainages found in all of the 27 counties of Caldas. This list recorded 133 species, 28 families and nine orders, of which 18 species are classified as endangered or threatened , 11 species are endemic to Colombia, and one new species is recorded for the country. Also listed are 17 species of fish used in pisciculture and 14 introduced species. It is possible that as research of fish resources progresses in the region, the inventory will significantly increase. It is hoped that this study will serve as a starting point for taxonomic, ecological and conservation of the fish fauna of the department.